North America [videorecording (DVD)] - Selleck, Tom, 1945- (Discovery Communications, 2013)
North America: where civilization collides with untamed wilderness. Just feet beyond our own back yards rages a spectacle we rarely see. Join us as we step into this hidden world teeming with life, across impossible mountains and endless deserts. Dive into unexplored forests and crash into rugged coasts. Unforgiving, brutal, yet achingly beautiful, this vast continent offers boundless rewards for those brave enough to take on this land and call her home.